Exploration of the Concept of Relation and Function in the Quran with the Theme of Q.S. Ar-Rahman - Dwi Setiawati Radjak; Muhammad Zia Alghar; Aam Choirotul Cholidiyah (West Science Islamic Studies, 2023)
Islamic value-integrated mathematics education not only plays a role in training students' thinking and reasoning but also forms a human personality that is faithful an31 2d pious to Allah SWT. This research aims to reveal the concept of relationship and function in Q.S. Ar-Rahman. The research was conducted with a qualitative approach with the type of literature study. The data was obtained through literature studies from the Quran, books, journals, proceedings, and scientific papers. The results showed the concept of relation and function in Q.S. Ar-Rahman. The concept of relation is found in the arrangement of letters to verse numbers and many letters to verse numbers. The concept of function found consists of bijective, surjective, and injective functions. The concepts of relation and function are then represented as graphs and ordered pairs. The results of this research can be used in learning mathematics material on relations and functions at junior high and senior high school levels.